Beginning Fedora desktop : Fedora 18 edition - Petersen, Richard, 1949- (Expert's voice in Linux., 2013)
Beginning Fedora Desktop: Fedora 18 Edition is a complete guide to using the Fedora 18 Desktop Linux release as your daily driver for mail, productivity, social networking, and more. Author and Linux expert Richard Petersen delves into the operating system as a whole and offers you a complete treatment of Fedora 18 Desktop installation, configuration, and use. You'll discover how to install Fedora 18 Desktop on any hardware, learn which applications perform which functions, how to manage software updates, tips and tricks for the GNOME 3 and KDE desktops, useful shell commands, and both the Fedora administration and network tools. Get the most out of Fedora 18 Desktop -- including free Office suites, editors, e-book readers, music and video applications and codecs, email clients, Web and FTP browsers, microblogging and IM applications -- with a copy of Beginning Fedora Desktop: Fedora 18 Edition at your side. What you'll learn how to install Fedora 18 Desktop on any hardware the available GUI choices, including KDE, GNOME, and alternative desktop environments how to use word processors, spreadsheets, presentation, and e-mail software how to maintain your system and back it up how to participate in social networks using open source clients and much more Who this book is for Beginning Fedora Desktop: Fedora 18 Edition is for novice to intermediate users who are looking to install Fedora 18 as their primary computing environment.